Treaty-making power of the Congress and the President of the Republic in Peru: some thoughts regarding the celebration of the Extradition Treaty between Peru and France - Méndez Chang, Elvira (2016)
This article reflects on the treaty-making power of the Congress and the President of the Republic in light of the Peruvian domestic law and International Law (particularly within the framework of the Vienna Convention of 1969 on the Law of Treaties) taking into account the discussions that arose betweenthe legislative and the executive powers regarding the ratification of the Extradition Treaty between Peru and France of 2016. The domestic law applicable to the conclusion of a treaty in Peru establishes that the President of the Republic is the only one who has the power to express the consent of the State to be bound by a treaty through ratification, which has internationallegal effects. The Congress has the power to approve treaties whose provisions are related to topics listed in Article 56 of 1993 Peruvian Constitution. The Congress’ legislative approval implies a parliamentary control regarding the acts of the President. However, Congress cannot compel the President to ratify a treaty (as it was discussed regarding the Extradition Treaty between Peru andFrance) neither issue the ratification.